ANALISIS KOMPARATIF PER DAN PBV SAHAM ADRO DAN ITMG SEBAGAI STRATEGI INVESTASI DI SEKTOR ENERGI BATU BARA - Asnahwati, Asnahwati; Nurwidyanti, Ferisca; Liyas, Jeli Nata (Komunitas Manajemen Kompetitif, 2025)
Stock valuation through financial ratios is one of the important indicators in fundamental analysis to assess the viability of a stock. This research aims to analyse and compare the valuation performance of two coal sector companies, namely PT Adaro Energy Indonesia Tbk (ADRO) and PT Indo Tambangraya Megah Tbk (ITMG), using the Price Earnings Ratio (PER) and Price to Book Value (PBV) ratios during the period 2019–2023. This research method uses a comparative descriptive quantitative approach with secondary data obtained from the annual financial reports published on the Indonesia Stock Exchange (IDX), as well as annual stock price data obtained from Yahoo Finance and RTI Business. Data analysis is conducted by calculating the PER and PBV of each company, followed by descriptive statistical analysis and an independent sample t-test to determine significant differences between the two stocks. The research results show that the average Price Earnings Ratio (PER) of ADRO is higher compared to ITMG, indicating greater market expectations for ADRO's earnings growth. However, statistical tests show that only the PER difference is significant, while the Price to Book Value (PBV) does not show a significant difference. These findings suggest that ITMG is more appealing to value investing investors, while ADRO is more relevant for growth investing oriented investors.